Applying the community capital framework for social entrepreneurial ecosystem development: Vietnam's One Commune One Product program. (4th May 2023) - Ho, Khanh Le Phi; Adhikari, Rajendra; Bonney, Laurie; Teo, Do Dang; Miles, Morgan P
ABSTRACT: This study explores the efficacy of Vietnam's One Commune, One Product (OCOP) program as a community development program. Participation in the OCOP program by rural enterprises resulted in increased stocks of community capital: (1) human capital through participation in training and workshops; (2) social capital through networking at OCOP workshops, training events, and trade fairs directly; and (3) financial capital due to enhanced livelihoods through domestic and exports sales of OCOP branded products. These social and economic outcomes result from the OCOP-enabled opportunities for participants to develop their business and entrepreneurial skills and access resources to build better livelihoods while developing their portfolio of community capital and enhancing their rural social and economic entrepreneurial ecosystem.